Peran Guru Pendidikan Agama Kristen dalam Memperbaiki Attitude dan Moralitas Peserta Didik - Gultom, Ayub Parakaleo; Parulyan , Hisar; Cinta, Yesa (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2025)
The descriptive qualitative method was used in this study to analyze the role of Christian Religious Education teachers in improving students' attitudes and morality by applying biblical values in their education. In addition, this study describes theoretically and practically how Christian Religious Education teachers can function as agents of transformation in shaping students' characters. Teachers not only serve as educators, but also serve as role models who demonstrate values such as love, honesty, responsibility and humility. Teaching Christian Religious Education can help shape student character by using a holistic approach that includes cognitive, affective, and psychomotor. Nonetheless, Christian Religious Education teachers face many problems, such as the negative impact of technology, society, and the family environment. Therefore, to overcome these problems, relevant, creative and contextual approaches are needed. In addition, this research emphasizes the importance of cooperation between teachers, parents and the school community to ensure that Christian values can be applied in students' daily lives. Christian Religious Education teachers can serve as agents of transformation in improving students' attitudes and morality effectively and consistently.